Nylon composite material, preparation method thereof and structural member

By using a combination of maleic anhydride grafted polyamide, glass fiber and laser additives in nylon composites, and through electron beam irradiation and heating reactions, the problems of material strength, toughness and laser marking clarity are solved, achieving efficient and economical preparation and application of nylon composites.

CN119752084APending Publication Date: 2025-04-04BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410195735.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

While improving strength and toughness, existing nylon composite materials are difficult to take into account the compatibility of laser additives and the mechanical properties of the material, and laser markings are prone to blur or wear.

Method used

The combination of maleic anhydride grafted polyamide, glass fiber and laser additives is used to form maleic anhydride grafted polyamide through electron beam irradiation and heating reaction, improving the compatibility of PA and laser additives, and forming a clear permanent mark on the surface of the material.

Benefits of technology

The comprehensive optimization of nylon composite materials in terms of strength, toughness and laser marking clarity is achieved, avoiding the negative impact of polyolefins on material strength, and improving the industrial production efficiency of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752084A_ABST
    Figure CN119752084A_ABST
Patent Text Reader

Abstract

The invention provides a nylon composite material, a preparation method thereof and a structural member. The nylon composite material comprises maleic anhydride grafted polyamide, glass fibers and a laser aid. The nylon composite material has high strength and excellent toughness, and clear pattern marks can be formed on the nylon composite material through laser irradiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to nylon composite materials and preparation methods and structural parts thereof. Background Art

[0002] Structural parts made of nylon composite materials are often used in automotive components, such as nylon intake manifolds used in fuel engines. Generally, in order to achieve the purpose of product traceability, the above-mentioned structural parts (such as intake manifolds) need to match laser markings, so the materials used to prepare the above-mentioned structural parts need to contain additives such as laser additives, which have poor compatibility with PA. In order to improve its compatibility with PA, the industry chooses polyolefins grafted with maleic anhydride as compatibilizers, but polyolefins will cause the mechanical properties of the material to decrease. Summary of the invention

[0003] In view of this, the embodiments of the present application provide a nylon composite material and a preparation method and a structural member thereof, which can have both high strength and excellent toughness, and laser irradiation can form a clear pattern mark on the nylon composite material.

[0004] A first aspect of an embodiment of the present application provides a nylon composite material, comprising polyamide grafted with maleic anhydride, glass fiber, and a laser auxiliary agent.

[0005] PA has excellent strength and certain toughness. Maleic anhydride grafted on the surface of PA can change the interfacial properties of PA. It can be used as a compatibilizer to improve the interfacial descriptive properties between PA and additives such as laser additives, so that a uniform nylon composite material can be obtained without using polyolefin grafted with maleic anhydride as a compatibilizer, thereby avoiding the negative impact of polyolefin on the strength of the nylon composite material. In addition, when the nylon composite material is irradiated with a laser, a clear permanent mark can be formed on the surface of the nylon composite material. Therefore, the above-mentioned nylon composite material can have both high strength and excellent toughness, and a clear permanent pattern can be formed on the surface of the material after laser irradiation, which can be used to provide an intake manifold with excellent comprehensive performance.

[0006] A second aspect of the embodiment of the present application provides a method for preparing a nylon composite material, comprising:

[0007] (1) mixing polyamide irradiated by electron beam with maleic anhydride in a vacuum environment, and heating the obtained mixture in a protective atmosphere to obtain polyamide grafted with maleic anhydride; or mixing polyamide with maleic anhydride, and subjecting the obtained mixture to electron beam irradiation in a vacuum environment to obtain polyamide grafted with maleic anhydride;

[0008] (2) The maleic anhydride grafted polyamide is mixed with glass fiber and a laser auxiliary agent to obtain a nylon composite material.

[0009] The preparation method is simple to operate, has strong process reliability and high production efficiency, and is suitable for large-scale industrial production.

[0010] The third aspect of the embodiment of the present application further provides a structural part, which includes the nylon composite material provided in the first aspect of the embodiment of the present application, or includes the nylon composite material prepared by the preparation method of the nylon composite material provided in the second aspect of the embodiment of the present application. In this way, the structural part can have both high strength and good toughness, and laser irradiation can form a clear permanent identification mark on the structural part. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is an optical photograph of the nylon composite material provided in Example 1 of the present application after laser marking;

[0012] Figure 2 This is an optical photograph of the nylon composite material provided in Example 5 of the present application after laser marking. DETAILED DESCRIPTION

[0013] For automotive components, the quality assurance of their structural parts is very critical. For example, a fuel engine generally has multiple cylinders. In order to distribute the mixture of air and fuel to each cylinder, an intake manifold is generally set between the carburetor or throttle body and the cylinder; it can be seen that the intake manifold is a very critical engine component. Therefore, the traceability of the intake manifold is also a key link in quality assurance. Traditional identification generally uses printing or heat transfer, embossing, etc. to form a mark on the surface of the intake manifold, but during long-term use, the content or pattern of the above-mentioned mark is very easy to blur or wear, or even fall off. In order to improve the above situation, laser marking is now mostly used to mark the intake manifold. In related technologies, in order to improve lightweight and reduce production costs, plastic intake manifolds are mostly used. This requires adding laser additives to the plastic, using lasers to irradiate the intake manifold, so that the laser additives on its surface undergo vaporization reactions or other chemical reactions accompanied by color changes, thereby leaving a permanent mark on the surface of the intake manifold.

[0014] At present, PA has gradually become the preferred material for intake manifolds due to its excellent mechanical properties, good oil resistance and chemical stability. However, laser additives are generally selected from inorganic substances, and nylon composite materials generally have other additives. The surface of these additives usually contains polar groups, which are not compatible with PA. The industry generally chooses maleic anhydride grafted polyolefin as a compatibilizer to promote the blending effect of PA with laser additives or other additives. However, the presence of polyolefin will reduce the strength of the material and affect the application of the intake manifold.

[0015] In order to solve the above technical problems, an embodiment of the present application provides a nylon composite material, including polyamide grafted with maleic anhydride, glass fiber and a laser auxiliary agent.

[0016] PA has excellent strength and certain toughness. The maleic anhydride grafted on the surface of PA contains a large number of polar groups, which can change the interfacial properties of PA. Specifically, based on the similar compatibility theory, the polar groups in maleic anhydride have good compatibility with the polar groups on the surface of other components, or can also react or form hydrogen bonds with the hydroxyl, amino or carboxyl groups that may exist on the surface of some components, so that maleic anhydride can be used as a compatibilizer to improve the interfacial properties between PA and laser additives and other additives, so that a uniform nylon composite material can be obtained without using maleic anhydride grafted polyolefin as a compatibilizer, thereby avoiding the negative impact of polyolefin on the strength of nylon composite materials. Glass fiber can effectively reduce the hygroscopicity and shrinkage of nylon composite materials, and improve the tensile strength and bending strength of nylon composite materials. In addition, when the nylon composite material is irradiated with a laser, the laser additive therein can undergo a chemical reaction, and the color of the nylon composite material in the area irradiated by the laser will change significantly, so that a clear permanent mark can be formed on the surface of the nylon composite material. Therefore, the nylon composite material provided in the embodiment of the present application can have both high strength (specifically including tensile strength and bending strength) and excellent toughness, and a clear permanent pattern can be formed on the surface of the material after laser irradiation, and can be used to provide an intake manifold with excellent comprehensive performance.

[0017] In the embodiment of the present application, the main components of the glass fiber include aluminum oxide, silicon dioxide, and calcium oxide. In the embodiment of the present application, the fibrous substance in the nylon composite material can be observed by scanning electron microscope (SEM); after the nylon composite material is calcined at 1000°C for 4 hours using a muffle furnace, the residual ash is subjected to elemental analysis to characterize the presence of glass fiber. In some embodiments of the present application, the glass fiber is an alkali-free glass fiber. The alkali-free glass fiber has a high elastic modulus and good rigidity, a large elongation within the elastic limit and high tensile strength, which is more conducive to improving the impact strength of the nylon composite material, and has good chemical resistance and low water absorption. In the embodiment of the present application, the alkali-free glass fiber includes a glass fiber having an alkali metal oxide content (e.g., potassium oxide, sodium oxide) of ≤1%. In some specific embodiments, the alkali-free glass fiber is a glass fiber having an alkali metal oxide content of ≤0.5%.

[0018] It is understandable that PA has different models, for example, PA6 (polycaprolactam), PA66 (polyhexamethylene adipamide), etc. The present application does not limit the specific model of PA, and each model of PA has its own characteristics. For example, the mechanical properties of PA6 and PA66 are equivalent, but the cost of PA6 is lower, and those skilled in the art can choose as needed. However, it should be noted that since the nylon material in the nylon composite material provided in the embodiment of the present application is PA grafted with maleic anhydride, it has good compatibility with laser additives and has low requirements for processing fluidity during its preparation process, a single PA6 can also be used to successfully obtain a nylon composite material with excellent performance and low cost.

[0019] In some embodiments of the present application, the mass proportion of polyamide PA in the nylon composite material is 55%-65%. The mass proportion of PA is controlled within the above range. First, it provides the nylon composite material with the physical and chemical properties of nylon as the main material, and second, it will not squeeze out the share of other components, such as the share of glass fiber, thereby ensuring the comprehensive performance of the nylon composite material. Specifically, the mass proportion of PA in the nylon composite material can be but is not limited to 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%.

[0020] In some embodiments of the present application, the mass proportion of maleic anhydride in the nylon composite material is 2%-5%. Controlling the mass proportion of maleic anhydride in the nylon composite material, that is, controlling the grafting rate of maleic anhydride on the surface of PA. The appropriate grafting rate can effectively improve the compatibility between PA and laser additives and other possible additives, improve the uniformity of the nylon composite material, optimize its performance, and will not cause unnecessary waste, and will not affect the mechanical strength of the nylon composite material. Specifically, the mass proportion of maleic anhydride in the nylon composite material can be, but is not limited to, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%.

[0021] It should be noted that in some cases, such as when it is necessary to improve the toughness of nylon composite materials while taking into account the mechanical properties, an appropriate amount of maleic anhydride grafted polyolefin can be added to replace maleic anhydride grafted PA. At this time, the mass proportion of polyolefin in the nylon composite material is controlled to be ≤1%; for example, 0.1%, 0.2%, 0.5%, 0.8%, etc.

[0022] Compared with the related art, since the compatibilizer used in the embodiment of the present application is maleic anhydride itself, there is no need to introduce polyolefins that affect strength, so, at a lower glass fiber content, higher or equivalent mechanical properties can be achieved. In other words, compared with the related art, at the same PA content and glass fiber content, the nylon composite material provided by the embodiment of the present application has higher strength (e.g., tensile strength and impact strength). In some embodiments of the present application, the mass proportion of glass fiber in the nylon composite material is 25%-35%. In this way, it is beneficial to improve the mechanical properties (e.g., strength), dimensional stability, heat resistance and aging resistance of the nylon composite material, and will not affect the performance of the PA properties in the nylon composite material, which is beneficial to the application of the final nylon composite material, especially the application of nylon composite materials in the field of intake manifolds. Specifically, the mass proportion of glass fiber in the nylon composite material can be, but is not limited to, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%.

[0023] In some embodiments of the present application, the diameter of the glass fiber is 7μm-13μm and the length is 3mm-4.5mm. In this way, it is not easy for the glass fibers to be entangled, and the reinforcing effect on PA is better. In addition, considering that the size of the glass fiber in the product depends on the size of the glass fiber raw material, the glass fiber with the above size has good processing performance, which is conducive to the preparation of nylon composite materials. Specifically, the diameter of the glass fiber can be but not limited to 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm. The length of the glass fiber can be but not limited to 3mm, 3.2mm, 3.5mm, 3.8mm, 4mm, 4.2mm, 4.5mm.

[0024] In some embodiments of the present application, the mass proportion of the laser additive in the nylon composite material is 0.2%-1%. In this way, when the nylon composite material is irradiated with a laser, a clear permanent pattern can be formed on the surface of the nylon composite material, and the physical and chemical properties of the nylon composite material will not be affected. Specifically, the mass proportion of the laser additive in the nylon composite material can be, but is not limited to, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%.

[0025] In the embodiments of the present application, any laser auxiliary agent known in the art can be used as the laser auxiliary agent. In some embodiments of the present application, the laser auxiliary agent is selected from metal salts and / or metal oxides; wherein the metal elements in the metal salts and the metal oxides include at least one of iron, copper, barium, calcium, manganese, chromium and potassium. The color development reaction of the above-mentioned laser auxiliary agent is excellent and will not affect the mechanical properties of the nylon composite material. In some specific embodiments, the above-mentioned laser auxiliary agent can be selected from metal compound laser auxiliary agents of models such as Merck 8835, HZ889, PA5903, and JYN8898. The above-mentioned laser auxiliary agents contain color powder, which can make the nylon composite material appear black or other dark colors. Therefore, there is no need to add carbon black, and therefore there is no need to use titanium dioxide, a laser auxiliary agent that affects the strength of nylon materials.

[0026] In order to further optimize the mechanical properties of nylon composite materials, nylon composite materials also include mechanical reinforcement materials. In some specific embodiments, the above-mentioned mechanical reinforcement materials include but are not limited to at least one of silica lime, mica powder and barium sulfate whiskers. The above-mentioned mechanical reinforcement materials can be well dispersed in the nylon material system, or the role of commonly used additives in the field can be evenly dispersed in the nylon composite material, and can effectively enhance the mechanical properties of the nylon composite material. In some specific embodiments, the mass proportion of mechanical reinforcement materials in nylon composite materials is 1%-3%. In this way, while improving the mechanical properties of nylon composite materials, the comprehensive performance of nylon composite materials can be guaranteed to be better. Specifically, the mass proportion of mechanical reinforcement materials in nylon composite materials can be but not limited to 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%.

[0027] In order to successfully prepare the nylon composite material or improve the comprehensive performance of the nylon composite material, other additives are generally required to be added, and these additives will remain in the nylon composite material product. In some embodiments of the present application, the nylon composite material also includes at least one of a lubricant, an antioxidant and a silane coupling agent.

[0028] Lubricants can promote the uniform dispersion of mechanical reinforcement materials (e.g., silica lime) in nylon composites and improve the uniformity of nylon composites. In some specific embodiments, the mass proportion of lubricants in nylon composites is 0.6%-1.5%. Specifically, the mass proportion of lubricants in nylon composites can be but is not limited to 0.6%, 0.8%, 1%, 1.2%, 1.5%. In some specific embodiments, lubricants include but are not limited to hyperbranched polymers and / or ethylene bis fatty acid amides. In the embodiments of the present application, hyperbranched polymers include highly branched but irregularly structured polymers composed of branching units. In the embodiments of the present application, the end groups of hyperbranched polymers include carboxyl groups, amine groups, hydroxyl groups, etc.

[0029] Antioxidants can improve the antioxidant properties of nylon composite materials. In some specific embodiments, the mass proportion of antioxidants in nylon composite materials is 0.2%-1%. In this way, it can be evenly dispersed and effectively improve the antioxidant properties of nylon composite materials, which is conducive to its promotion and application. Specifically, the mass proportion of antioxidants in nylon composite materials can be, but not limited to, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%. In the embodiment of the present application, the above-mentioned antioxidants can be selected from any antioxidant known in the art, for example, including but not limited to at least one of hindered phenol antioxidants, phosphite antioxidants, amine antioxidants, and copper salt antioxidants. In order to optimize its antioxidant effect, in some specific embodiments, the antioxidant is selected from at least one of a combination of hindered phenol antioxidants and phosphite antioxidants, a combination of amine antioxidants and phosphite antioxidants, and a copper salt antioxidant.

[0030] Silane coupling agent can promote the dispersion of glass fiber in nylon composite material, improve the uniformity of nylon composite material, and improve its processing performance. In the embodiment of the present application, the above-mentioned silane coupling agent can be selected from any silane coupling agent known in the art that can promote the dispersion of glass fiber, for example, γ-glycidyl ether oxypropyl trimethoxy silane. In order to ensure that the comprehensive performance of nylon composite material is better, in some specific embodiments, the mass proportion of silane coupling agent in nylon composite material is controlled to be 0.2%-1%. Specifically, the mass proportion of silane coupling agent in nylon composite material can be but not limited to 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%. It should be noted that in the embodiment of the present application, the silane coupling agent in nylon composite material exists in the form of a single substance.

[0031] In some embodiments of the present application, the nylon composite material includes maleic anhydride grafted polyamide, glass fiber, laser auxiliary agent, mechanical reinforcement material, lubricant, antioxidant and silane coupling agent. In some specific embodiments, the nylon composite material includes the following components in mass proportion: 55%-65% polyamide, 2%-5% maleic anhydride, 25%-35% glass fiber, 0.2%-1% laser auxiliary agent, 1%-3% mechanical reinforcement material, 0.6%-1.5% lubricant, 0.2%-1% antioxidant, 0.2%-1% silane coupling agent. In the embodiment of the present application, a certain amount of nylon composite material can be burned at 1000°C for 4h in a muffle furnace, and the mass of the remaining ash is weighed, (mass of ash / total mass of nylon composite material before burning) × 100%, and the mass proportion of glass fiber in the nylon composite material can be obtained. Thermogravimetry analysis (TG) can be used to test the mass proportion of maleic anhydride in nylon composite materials. Specifically, the TG test is carried out in a nitrogen atmosphere, with the temperature rising from 25°C to 800°C at a heating rate of 10°C / min.

[0032] Accordingly, the present embodiment provides a method for preparing a nylon composite material, which can be used to prepare the aforementioned nylon composite material provided in the present embodiment, and the preparation method comprises:

[0033] S01: including method (a) or method (b), wherein:

[0034] Method (a) includes: mixing the polyamide irradiated by electron beam with maleic anhydride in a vacuum environment, and heating the obtained mixture in a protective atmosphere to obtain maleic anhydride grafted polyamide; in the embodiment of the present application, the polyamide needs to be irradiated in a vacuum environment.

[0035] Method (b) comprises: mixing polyamide and maleic anhydride, and subjecting the obtained mixture to electron beam irradiation in a vacuum environment to obtain maleic anhydride grafted polyamide;

[0036] S02: The maleic anhydride grafted polyamide prepared in the above method (a) or method (b) is mixed with glass fiber and laser auxiliary agent to obtain a nylon composite material.

[0037] The preparation method is simple to operate, has strong process reliability and high production efficiency, and is suitable for large-scale industrial production.

[0038] In the above step S01, electron beam irradiation can cause the surface of the polyamide material to quickly form active free radicals centered on carbon atoms, which can react with maleic anhydride to obtain maleic anhydride grafted polyamide. Electron beam irradiation is not affected by parameters such as the shape and molecular weight of the grafted material (i.e., PA), is easy to operate, has a high grafting rate, and can also improve the uniformity of maleic anhydride grafted on the surface of the polyamide, which is more conducive to the preparation of nylon composite materials and the performance of the prepared nylon composite materials.

[0039] Further, for method (a), the polyamide is irradiated with an electron beam and then mixed with maleic anhydride, and free radicals are formed on the surface of the polyamide. Maleic anhydride needs to react with the above-mentioned active free radicals under heating conditions to be grafted on the surface of PA, but this method is more conducive to reducing the risk of side reactions (for example, cross-linking reactions) between maleic anhydride molecules. For method (b), maleic anhydride is first mixed with PA, and then the mixture is irradiated with an electron beam. It can be understood that while electron beam irradiation provides energy to generate free radicals in PA, it can also generate free radicals in maleic anhydride. Therefore, maleic anhydride can be grafted on the surface of PA during irradiation. Therefore, when method (b) is adopted, there is no need to heat the mixture after irradiation.

[0040] In some embodiments of the present application, in the above-mentioned method (a), the polyamide after electron beam irradiation is mixed with the maleic anhydride solution, and the mass content of maleic anhydride in the solution is controlled to be 30%-70%. In this way, the grafting rate of maleic anhydride can be guaranteed while improving production efficiency, and the risk of side reactions between maleic anhydrides can be fully avoided. Specifically, for method (a), the mass content of maleic anhydride in the above-mentioned solution can be, but not limited to, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%. In the embodiment of the present application, the solvent type of maleic anhydride solution is not limited, and the solvent is a good solvent for maleic anhydride and will not react with maleic anhydride and PA under electron beam irradiation.

[0041] In the embodiment of the present application, in the method (b), subjecting the mixture of polyamide and maleic anhydride to electron beam irradiation in a vacuum environment comprises: placing the mixture of polyamide and maleic anhydride in a vacuum bag, evacuating the bag, and then irradiating the bag with electron beam. In the embodiment of the present application, the mixing of polyamide and maleic anhydride can be, but is not limited to, carried out in a blender.

[0042] In some embodiments of the present application, in the above method (a), the polyamide irradiated by electron beam is mixed with a solution of maleic anhydride, and the obtained mixture is heated under a protective atmosphere, and the heating includes: heating at 50°C-80°C for 1h-8h. In this way, the risk of side reactions can be reduced while taking into account the grafting efficiency. Specifically, the above heating temperature can be but not limited to 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, 80°C. The above heating time can be but not limited to 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h.

[0043] The free radical concentration on the PA surface can be regulated by the irradiation dose of the electron beam. Considering that after the free radicals are generated, there is also a mixing process. During heating, some free radicals may be deactivated. Therefore, in order to ensure the final grafting rate of maleic anhydride, in some embodiments of the present application, in the above-mentioned method (a), the irradiation dose of the electron beam irradiation is 30kGy-180kGy. Specifically, in the method (a), the irradiation dose of the electron beam irradiation can be, but is not limited to, 30kGy, 40kGy, 50kGy, 60kGy, 70kGy, 80kGy, 90kGy, 100kGy, 110kGy, 120kGy, 130kGy, 140kGy, 150kGy, 160kGy, 170kGy, 180kGy. In some specific embodiments, in order to take into account both grafting efficiency and production efficiency, in mode (a), the irradiation dose rate of electron beam irradiation is 30 kGy / pass-90 kGy / pass. Specifically, in mode (a), the irradiation dose rate of electron beam irradiation can be, but is not limited to, 30 kGy / pass, 40 kGy / pass, 50 kGy / pass, 60 kGy / pass, 70 kGy / pass, 80 kGy / pass, 90 kGy / pass.

[0044] Based on the method (b), the mixture of polyamide and maleic anhydride is subjected to electron beam irradiation. In this process, the possibility of deactivation of free radicals on the surface of PA is small, and the risk of side reactions between maleic anhydrides under electron irradiation is relatively high compared with the method (a). Therefore, in the method (b), the irradiation dose of the electron beam irradiation is controlled to be 10kGy-80kGy, and the irradiation dose rate is 5kGy / pass-40kGy / pass. In this way, the risk of side reactions between maleic anhydrides can be reduced. Specifically, in the method (b), the irradiation dose of the electron beam irradiation can be, but is not limited to, 10kGy, 20kGy, 30kGy, 40kGy, 50kGy, 60kGy, 70kGy, 80kGy. In method (b), the irradiation dose rate of electron beam irradiation is controlled to 5 kGy / pass, 10 kGy / pass, 15 kGy / pass, 20 kGy / pass, 25 kGy / pass, 30 kGy / pass, 35 kGy / pass, and 40 kGy / pass.

[0045] In method (b), PA is first mixed with a maleic anhydride solution, and the resulting mixture is subjected to electron beam irradiation. Similarly, in order to reduce the risk of side reactions between maleic anhydrides and take into account the grafting efficiency, in method (b), the mass content of maleic anhydride in the solution is 4%-40%. Specifically, in method (b), the mass content of maleic anhydride in the solution can be, but is not limited to, 4%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%.

[0046] In some embodiments of the present application, before step S02, the material obtained by method (a) or method (b) is washed and dried with deionized water to remove the maleic anhydride adsorbed on the surface of PA that has not been successfully grafted, thereby obtaining maleic anhydride grafted PA.

[0047] In the above step S02, the process of mixing the polyamide grafted with maleic anhydride, glass fiber and laser auxiliary agent can be any process known in the art. In some embodiments, the above components are mixed using a high-speed mixer, a twin-screw extruder, etc. Specifically, the components are mixed using a high-speed mixer and a twin-screw extruder. It is understandable that the twin-screw extruder generally includes at least two feed ports. In some specific embodiments, the polyamide of maleic anhydride and the laser auxiliary agent are first mixed in a high-speed mixer to obtain a first mixed material, and then the first mixed material is put into the twin-screw extruder from the first feed port of the twin-screw extruder, and the glass fiber is put into the twin-screw extruder from the second feed port of the twin-screw extruder, and the first mixed material and the glass fiber are melt-extruded, cooled, and a nylon composite material is obtained.

[0048] During the above mixing process, the parameters of the high-speed mixer and the twin-screw extruder can be set by a person skilled in the art according to the actual production conditions and the parameters they are familiar with. In some specific embodiments, in order to optimize the mixing effect, the processing temperature of the twin-screw extruder is controlled to be 220°C-260°C, the head temperature of the twin-screw extruder is 235°C-250°C, and the screw speed is 400r / min-430r / min.

[0049] In the embodiment of the present application, the above cooling process can be a process well known to technicians in the field, such as water cooling, air cooling, etc.

[0050] In some cases, in order to facilitate the subsequent application of the nylon composite material, the cooled nylon composite material needs to be cut into pellets.

[0051] In some embodiments of the present application, step S02 further includes mixing other additives with PA grafted with maleic anhydride, laser additives and glass fiber. At this time, other additives can be mixed with PA grafted with maleic anhydride and laser additives to obtain a first mixture, and then the first mixture is mixed with glass fiber. For details, please refer to the relevant description in the previous text, which will not be repeated here. Specifically, the above-mentioned other additives include at least one of a mechanical reinforcement material, a lubricant, an antioxidant and a silane coupling agent.

[0052] The present application also provides a structural part, which includes the nylon composite material provided in the present application, or includes the nylon composite material prepared by the preparation method of the nylon composite material provided in the present application. In this way, the structural part can have both high strength and good toughness, and laser irradiation can form a clear permanent identification mark on the structural part.

[0053] In some embodiments of the present application, a permanent laser mark is formed on the structural member. The mark can be text, a pattern, and the pattern can be a QR code or the like.

[0054] In some embodiments of the present application, the above-mentioned structural component is an intake manifold.

[0055] The technical solution of the present application is further illustrated by multiple embodiments below.

[0056] Example 1

[0057] (1) Polyamide (specifically PA6) is irradiated with electron beam, the irradiation dose is 30 kGy, and the irradiation dose rate is 30 kGy / pass. The irradiated PA is mixed with a 70% by mass maleic anhydride solution, and heated at 80° C. for 1 hour under a protective atmosphere. The material obtained after the heating reaction is then washed and dried with deionized water to obtain maleic anhydride grafted PA.

[0058] (2) The obtained maleic anhydride grafted PA, laser auxiliary agent (specifically Merck 855), mechanical reinforcement material (specifically wollastonite), lubricant-ethylene bis fatty acid amide and hyperbranched polymer (Xingbeida Shanghai Chemical Material Co., Ltd., PA209), antioxidant (specifically BRUGGOLEN H3336 copper salt of Germany), silane coupling agent (specifically γ-glycidyl ether oxypropyl trimethoxy silane) are mixed in a high-speed mixer to obtain a first mixed material, and then the first mixed material and glass fiber (specifically alkali-free glass fiber with a diameter of 7μm-13μm and a length of 3mm-4.5mm) are placed in a twin-screw extruder for melt extrusion to obtain a nylon composite material. The processing temperature of the twin-screw extruder is as follows: 220°C for zone 1, 240°C for zone 2, 240°C for zone 3, 240°C for zone 4, 240°C for zone 5, 235°C for zone 6, 235°C for zone 7, and 235°C for zone 8. The die temperature is 235°C and the screw speed is 430r / min.

[0059] In the obtained nylon composite material, the mass proportion of PA6 is 61.7%, the mass proportion of maleic anhydride is 3%, the mass proportion of glass fiber is 30%, the mass proportion of laser auxiliary agent is 0.4%, the mass proportion of ethylenebisfatty acid amide is 0.4%, the mass proportion of hyperbranched polymer is 0.6%, the mass proportion of antioxidant is 0.4%, the mass proportion of wollastonite is 3%, and the mass proportion of silane coupling agent is 0.5%.

[0060] Example 2

[0061] The only difference from Example 1 is that in step (1), the polyamide (specifically PA6) is irradiated with an electron beam, the irradiation dose is 180 kGy, and the irradiation dose rate is 90 kGy / pass. The irradiated PA is mixed with a 30% by mass maleic anhydride solution, and heated at 50° C. for 8 hours under a protective atmosphere, and the material obtained after the heating reaction is washed and dried with deionized water to obtain maleic anhydride grafted PA.

[0062] In the nylon composite material, the mass proportion of PA6 is 55%, the mass proportion of maleic anhydride is 4.7%, the mass proportion of glass fiber is 35%, the mass proportion of laser auxiliary agent is 0.4%, the mass proportion of ethylenebisfatty acid amide is 0.4%, the mass proportion of hyperbranched polymer is 0.6%, the mass proportion of antioxidant is 0.4%, the mass proportion of wollastonite is 3%, and the mass proportion of silane coupling agent is 0.5%.

[0063] Example 3

[0064] The only difference from Example 1 is that in the nylon composite material, the mass proportion of PA6 is 65%, the mass proportion of maleic anhydride is 3%, the mass proportion of glass fiber is 26.7%, the mass proportion of laser auxiliary agent is 0.4%, the mass proportion of ethylenebisfatty acid amide is 0.4%, the mass proportion of hyperbranched polymer is 0.6%, the mass proportion of antioxidant is 0.4%, the mass proportion of wollastonite is 3%, and the mass proportion of silane coupling agent is 0.5%.

[0065] Example 4

[0066] The difference from Example 1 is that in step (1), the polyamide (specifically PA6) is irradiated with an electron beam, the irradiation dose is 180 kGy, and the irradiation dose rate is 90 kGy / pass. The irradiated PA is mixed with a 30% by mass maleic anhydride solution, and heated at 50° C. for 8 hours under a protective atmosphere, and the material obtained after the heating reaction is washed and dried with deionized water to obtain maleic anhydride grafted PA.

[0067] In the nylon composite material, the mass proportion of PA6 is 65%, the mass proportion of maleic anhydride is 3%, the mass proportion of glass fiber is 25%, the mass proportion of laser auxiliary agent is 0.4%, the mass proportion of ethylenebisfatty acid amide is 0.4%, the mass proportion of hyperbranched polymer is 0.6%, the mass proportion of antioxidant is 0.4%, the mass proportion of wollastonite is 3%, and the mass proportion of silane coupling agent is 0.5%.

[0068] Example 5

[0069] The difference from Example 1 is that carbon black is also added to the first mixture, and the ratio is fine-tuned. In the final nylon composite material, the mass proportion of PA6 is 61.1%, the mass proportion of maleic anhydride is 3%, the mass proportion of carbon black is 0.6%, the mass proportion of glass fiber is 30%, the mass proportion of laser auxiliary agent is 0.4%, the mass proportion of ethylenebisfatty acid amide is 0.4%, the mass proportion of hyperbranched polymer is 0.6%, the mass proportion of antioxidant is 0.4%, the mass proportion of wollastonite is 3%, and the mass proportion of silane coupling agent is 0.5%.

[0070] Example 6

[0071] The difference from Example 1 is that in step (1), the irradiation dose is 20 kGy and the irradiation dose rate is 20 kGy / pass. The irradiated PA is mixed with a 25% by mass maleic anhydride solution.

[0072] In the obtained nylon composite material, the mass proportion of PA6 is 63.7%, the mass proportion of maleic anhydride is 1%, the mass proportion of glass fiber is 30%, the mass proportion of laser auxiliary agent is 0.4%, the mass proportion of ethylenebisfatty acid amide is 0.4%, the mass proportion of hyperbranched polymer is 0.6%, the mass proportion of antioxidant is 0.4%, the mass proportion of wollastonite is 3%, and the mass proportion of silane coupling agent is 0.5%.

[0073] Example 7

[0074] The difference from Example 1 is that in step (1), the irradiation dose is 300 kGy and the irradiation dose rate is 100 kGy / pass. The irradiated PA is mixed with 80% by mass maleic anhydride solution.

[0075] In the obtained nylon composite material, the mass proportion of PA6 is 56.7%, the mass proportion of maleic anhydride is 6%, the mass proportion of glass fiber is 30%, the mass proportion of laser auxiliary agent is 0.4%, the mass proportion of ethylenebisfatty acid amide is 0.4%, the mass proportion of hyperbranched polymer is 0.6%, the mass proportion of antioxidant is 0.4%, the mass proportion of wollastonite is 3%, and the mass proportion of silane coupling agent is 0.5%.

[0076] Example 8

[0077] (1) PA6 and 4% by mass maleic anhydride solution were mixed in a blender, the resulting mixture was sealed in a vacuum bag and evacuated, and then the mixture was irradiated with an electron beam, the irradiation dose was 10 kGy, and the irradiation dose rate was 5 kGy / pass.

[0078] (2) The obtained maleic anhydride grafted PA is mixed with a laser auxiliary agent (specifically HZ889), a mechanical reinforcement material (specifically wollastonite), a lubricant - ethylenebis fatty acid amide and a hyperbranched polymer (Weihai Chenyuan Molecular New Materials Co., Ltd., CYD701), an antioxidant (specifically Revonox-608 phosphite antioxidant and Irganox245 hindered phenol antioxidant), and a silane coupling agent (specifically γ-glycidyloxypropyltrimethoxysilane) in a high-speed mixer to obtain a first mixture, and then the first mixture and glass fiber (specifically alkali-free glass fiber with a diameter of 7μm-13μm and a length of 3mm-4.5mm) are placed in a twin-screw extruder for melt extrusion to obtain a nylon composite material. The processing temperature of the twin-screw extruder is as follows: zone 1 235°C, zone 2 236°C, zone 3 236°C, zone 4 237°C, zone 5 260°C, zone 6 231°C, zone 7 225°C, zone 8 235°C. The die head temperature is 250°C, and the screw speed is 400r / min.

[0079] In the nylon composite material, the mass proportion of PA6 is 62.7%, the mass proportion of maleic anhydride is 2%, the mass proportion of glass fiber is 30%, the mass proportion of laser auxiliary agent is 0.4%, the mass proportion of ethylenebisfatty acid amide is 0.4%, the mass proportion of hyperbranched polymer is 0.6%, the mass proportion of antioxidant is 0.4%, the mass proportion of wollastonite is 3%, and the mass proportion of silane coupling agent is 0.5%.

[0080] Example 9

[0081] The difference from Example 7 is that in step (1), a 40% by mass maleic anhydride solution is used instead. In the final nylon composite material, the mass percentage of PA6 is 60%, the mass percentage of maleic anhydride is 5%, and the mass percentage of glass fiber is 29.7%.

[0082] Example 10

[0083] The difference from Example 8 is that in step (1), a 10% by mass maleic anhydride solution is used instead, the electron beam irradiation dose is 80 kGy, and the irradiation dose rate is 40 kGy / pass. In the final nylon composite material, the mass proportion of PA6 is 61.9%, the mass proportion of maleic anhydride is 3%, and the mass proportion of laser auxiliary agent is 0.2%.

[0084] Embodiment 11

[0085] The difference from Example 8 is that in step (1), a 10% by mass maleic anhydride solution is used instead, the electron beam irradiation dose is 80 kGy, and the irradiation dose rate is 40 kGy / pass. In the final nylon composite material, the mass proportion of PA6 is 61.1%, the mass proportion of maleic anhydride is 3%, and the mass proportion of laser auxiliary agent is 1%.

[0086] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.

[0087] Comparative Example 1

[0088] (1) Polyamide (specifically PA6), a compatibilizer (specifically a polyolefin grafted with maleic anhydride), a laser auxiliary agent (specifically HZ889), a mechanical reinforcing material (specifically wollastonite), a lubricant (specifically ethylenebisfatty acid amide and a hyperbranched polymer), an antioxidant (specifically H3336), and a silane coupling agent (specifically γ-glycidyloxypropyltrimethoxysilane) are mixed in a high-speed mixer to obtain a first mixture.

[0089] (2) The first mixed material and glass fiber (specifically, alkali-free glass fiber with a diameter of 7 μm-13 μm and a length of 3 mm-4.5 mm) are placed in a twin-screw extruder for melt extrusion to obtain a nylon composite material. The processing temperature of the twin-screw extruder is as follows: 220°C for zone 1, 240°C for zone 2, 240°C for zone 3, 240°C for zone 4, 240°C for zone 5, 235°C for zone 6, 235°C for zone 7, and 235°C for zone 8. The die head temperature is 235°C, and the screw speed is 430 r / min.

[0090] In the obtained nylon composite material, the mass proportion of PA6 is 61.7%, the mass proportion of the compatibilizer is 3%, the mass proportion of the glass fiber is 30%, the mass proportion of the laser auxiliary agent is 0.4%, the mass proportion of ethylenebisfatty acid amide is 0.4%, the mass proportion of the hyperbranched polymer is 0.6%, the mass proportion of the antioxidant is 0.4%, the mass proportion of wollastonite is 3%, and the mass proportion of the silane coupling agent is 0.5%.

[0091] Performance Testing

[0092] (1) Tensile property test: The tensile strength of the nylon composite materials of each embodiment and comparative example was tested using a universal tensile testing machine according to ASTM D638. During the test, the gauge length of each test sample was 50 mm, the load acceleration was 5 mm / min, and the sample was continuously loaded until it was completely broken to obtain the tensile strength of each sample. Five samples were tested in each group and the average value was taken. The results are summarized in Table 1.

[0093] (2) Flexural Strength Test: The flexural strength of the nylon composite materials of each embodiment and comparative example was tested using a universal tensile testing machine according to ASTM D790. During the test, the gauge length of each test sample was 50 mm, the load acceleration was 5 mm / min, and the sample was continuously loaded until it completely broke to obtain the flexural strength of each sample. Five samples were tested in each group and the average value was taken. The results are summarized in Table 1.

[0094] (3) Impact resistance test: According to ASTM D256, test specimens of the nylon composite materials of the embodiments and comparative examples were prepared. The test specimens had a notch bottom radius of 0.25 mm ± 0.12 mm and were 80 mm long, 4 mm wide and 10 mm high strips. The cantilever beam impact toughness test method was adopted. The pendulum energy was set to 2.75 J. The strips were fixed so that the notch of the strips faced the side of the pendulum impact edge. The pendulum was released and the impact energy absorbed by each specimen was recorded. The results are summarized in Table 1.

[0095] (4) Laser effect test: Laser test was performed on each embodiment and comparative example, and the same marking pattern was formed on the surface using the same laser parameters. The optical photographs of the nylon composite materials of embodiment 1 and embodiment 5 are shown in FIG. Figure 1 and Figure 2 The results show that the nylon composite material provided in the embodiment of the present application can achieve a clear laser marking effect, and not adding carbon black is more conducive to improving the clarity of the mark.

[0096] Table 1

[0097] Case Tensile strength(MPa) Bending strength(MPa) Absorbed impact energy (J / m) Example 1 167.9 248.8 112.2 Example 2 172.8 252.4 127.4 Example 3 163.7 245.4 135.5 Example 4 161.5 246.2 157.7 Example 5 168.2 247.6 111.5 Example 6 162.3 235.9 97.7 Example 7 160.4 244.6 140.9 Example 8 160.6 240.8 76.8 Example 9 166.8 247.7 148.3 Example 10 168.1 249.6 115.7 Embodiment 11 167.5 247.9 111.1 Comparative Example 1 155.2 230.7 125.3

[0098] From the results in Table 1, it can be seen that the preparation method provided in the examples of the present application can produce nylon composite materials with excellent performance. When only the type of compatibilizer is changed, the mechanical properties of the nylon composite materials produced in the examples are better than those in comparative example 1, which fully demonstrates the beneficial effects of the technical solution of the present application.

[0099] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A nylon composite material, characterized in that: It includes maleic anhydride grafted polyamide, glass fiber and laser additives.

2. The nylon composite material according to claim 1, characterized in that: Based on the mass of the nylon composite material, the mass of the polyamide accounts for 55%-65%, the mass of the maleic anhydride accounts for 2%-5%, the mass of the glass fiber accounts for 25%-35%, and the mass of the laser auxiliary agent accounts for 0.2%-1%.

3. The nylon composite material according to claim 1 or 2, characterized in that: The glass fiber has a diameter of 7 μm-13 μm and a length of 3 mm-4.5 mm; the glass fiber is selected from alkali-free glass fiber.

4. The nylon composite material according to any one of claims 1 to 3, characterized in that: The laser auxiliary agent includes metal salts and / or metal oxides; wherein the metal elements in the metal salts and the metal oxides include at least one of iron, copper, barium, calcium, manganese, chromium and potassium.

5. The nylon composite material according to any one of claims 1 to 4, characterized in that: The nylon composite material also includes a mechanical reinforcement material, which includes at least one of wollastonite, mica powder and barium sulfate whiskers; the weight proportion of the mechanical reinforcement material in the nylon composite material is 1%-3%.

6. The nylon composite material according to any one of claims 1 to 5, characterized in that: The nylon composite material further comprises at least one of a lubricant, an antioxidant and a silane coupling agent.

7. A method for preparing a nylon composite material, characterized in that: include: (1) mixing polyamide irradiated by electron beam with maleic anhydride in a vacuum environment, and heating the obtained mixture in a protective atmosphere to obtain polyamide grafted with maleic anhydride; or mixing polyamide with maleic anhydride, and subjecting the obtained mixture to electron beam irradiation in a vacuum environment to obtain polyamide grafted with maleic anhydride; (2) The maleic anhydride grafted polyamide is mixed with glass fiber and a laser auxiliary agent to obtain a nylon composite material.

8. The preparation method according to claim 7, characterized in that: The method of irradiating the polyamide with electron beam and then mixing it with maleic anhydride comprises: The irradiation dose of the electron beam irradiation is 30 kGy-180 kGy, and the irradiation dose rate is 30 kGy / pass-90 kGy / pass; The polyamide irradiated by the electron beam is mixed with a maleic anhydride solution having a mass content of 30% to 70%.

9. The preparation method according to claim 7 or 8, characterized in that: The heating comprises: heating at 50° C.-80° C. for 1 h-8 h.

10. The preparation method according to claim 7, characterized in that: The step of mixing the polyamide and maleic anhydride and subjecting the obtained mixture to electron beam irradiation comprises: The polyamide is mixed with a maleic anhydride solution having a mass content of 4% to 40%; The irradiation dose of the electron beam irradiation is 10 kGy-80 kGy, and the irradiation dose rate is 5 kGy / pass-40 kGy / pass.

11. A structural member, characterized in that: The structural member comprises the nylon composite material as described in any one of claims 1 to 6, or comprises the nylon composite material prepared by the preparation method as described in any one of claims 7 to 10.

12. The structural member according to claim 11, characterized in that: The structural component is an intake manifold.